Novel routes towards bioplastics from plants: elucidation of the methylperillate biosynthesis pathway from Salvia dorisiana trichomes. (24th February 2020) - Jongedijk, Esmer; Müller, Sebastian; van Dijk, Aalt D J; Schijlen, Elio; Champagne, Antoine; Boutry, Marc; Levisson, Mark; van der Krol, Sander; Bouwmeester, Harro; Beekwilder, Jules
Abstract : Monoterpene methylperillate can be used efficiently as a convenient starting material for polyethylene terephthalate plastic. We describe a biosynthetic pathway towards methylperillate from Salvia and report enzymes for key reactions. Abstract: Plants produce a large variety of highly functionalized terpenoids. Functional groups such as partially unsaturated rings and carboxyl groups provide handles to use these compounds as feedstock for biobased commodity chemicals. For instance, methylperillate, a monoterpenoid found in Salvia dorisiana, may be used for this purpose, as it carries both an unsaturated ring and a methylated carboxyl group. The biosynthetic pathway of methylperillate in plants is still unclear. In this work, we identified glandular trichomes from S. dorisiana as the location of biosynthesis and storage of methylperillate. mRNA from purified trichomes was used to identify four genes that can encode the pathway from geranyl diphosphate towards methylperillate. This pathway includes a (–)-limonene synthase (SdLS), a limonene 7-hydroxylase (SdL7H, CYP71A76), and a perillyl alcohol dehydrogenase (SdPOHDH). We also identified a terpene acid methyltransferase, perillic acid O- methyltransferase (SdPAOMT), with homology to salicylic acid OMTs. Transient expression in Nicotiana benthamiana of these four genes, in combination with a geranyl diphosphate synthase to boost precursor formation, resulted in production of methylperillate. This demonstrates the potential of these enzymes for metabolic engineering of a feedstock for biobased commodity chemicals.